2015
DOI: 10.3390/ijerph120100986
|View full text |Cite
|
Sign up to set email alerts
|

Risk Communication Concerning Welding Fumes for the Primary Preventive Care of Welding Apprentices in Southern Brazil

Abstract: This study’s aim was to assess the perceptions of welding apprentices concerning welding fumes being associated with respiratory and cardiovascular disorders and assess the implementation of risk communication as a primary prevention tool in the welding training process. This quasi-experimental, non-randomized study with before-and-after design was conducted with 84 welding apprentices in Southern Brazil. Poisson Regression analysis was used. Relative Risk was the measure used with a 95% confidence interval an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Fumes are very fine particles with a diameter of less than one micron which are produced by condensation of metal vapor during welding [67]. Fumes include a complex of different metal particles such as lead, ferrous, magnesium, zinc, beryllium, chromium, nickel, cobalt, cadmium, titanium, vanadium, antimony, and copper [8]. There have been increasing concerns about the harmful effects of welding fumes on the health of welders [9].…”
Section: Introductionmentioning
confidence: 99%
“…Fumes are very fine particles with a diameter of less than one micron which are produced by condensation of metal vapor during welding [67]. Fumes include a complex of different metal particles such as lead, ferrous, magnesium, zinc, beryllium, chromium, nickel, cobalt, cadmium, titanium, vanadium, antimony, and copper [8]. There have been increasing concerns about the harmful effects of welding fumes on the health of welders [9].…”
Section: Introductionmentioning
confidence: 99%
“…The multiplicity of factors, such as heat, burns, radiation (ultraviolet, visible and infrared), noise, gases, electrocution, uncomfortable postures involved in the work, the great variability in the chemical composition of welding fumes, the method used, the surrounding environment and the routes by which these harmful agents enter the body make this occupation a potential health hazard for the welder [1] [4]- [9]. Ocular morbidities, including ocular arc, photokeratitis, double vision and retinal damage related to the welding occupation are common among welders [2] [10] [11]. The limitations of this study were that clinical consultation was not made to determine the sequellar lesions of the ocular involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with current literature on the topic. Previous studies on apprentices and practicing farmers [32][33][34], hairdressers [35][36][37] and welders [38,39] have reported that knowledge about preventive measures varies from poor to average, the use of PPE is low, and several types of interventions tend to increase the level of knowledge and compliance with preventive measures. Kim et al [32] demonstrated in a pilot study among farmers that one educational workshop consisting of rotating stations with information on causes of work-related asthma, spirometry and use of PPE, aiming at increasing the knowledge about safety training and occupational health and safety (OHS) was feasible and effective, while Levesque et al [33] showed that farmers who received traditional pesticide safety training were more likely to use PPE; however, their confidence intervals were wide due to low number of participants.…”
Section: Discussionmentioning
confidence: 99%